2016
DOI: 10.1111/jan.12934
|View full text |Cite
|
Sign up to set email alerts
|

Primary caregivers of in‐home oxygen‐dependent children: predictors of stress based on characteristics, needs and social support

Abstract: Aim. To identify the predictors of primary caregivers' stress in caring for in-home oxygen-dependent children by examining the association between their levels of stress, caregiver needs and social support. Background. Increasing numbers of primary caregivers of oxygen-dependent children experience caregiving stress that warrants investigation. Design. The study used a cross-sectional design with three psychometric scalesModified-Parenting Stress Index, Caregiver Needs Scale and Social Support Index. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 25 publications
4
22
1
Order By: Relevance
“…The literature has pointed out that nurses' burnout is associated with the Big-Five factors of personality (Adriaenssens et al, 2015;Alarcon et al, 2009;Cañadas-De la Fuente et al, 2015). In particular, emotional stability has been established as associated with compassion fatigue, this is consistent with other studies showing that burnout is greatly need to face with the families who often reported experiencing a high level of emotional stress and uncertainty due to their child's critical stage and the frequency and severity of discomfort symptoms (Wang, Chen, et al, 2016;Wang, Lin, et al, 2016). Therefore, support resources to enhance emotional stability and offer social connection available for paediatric nurses are important to help them dealing with conflicts and hardship in work and life.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The literature has pointed out that nurses' burnout is associated with the Big-Five factors of personality (Adriaenssens et al, 2015;Alarcon et al, 2009;Cañadas-De la Fuente et al, 2015). In particular, emotional stability has been established as associated with compassion fatigue, this is consistent with other studies showing that burnout is greatly need to face with the families who often reported experiencing a high level of emotional stress and uncertainty due to their child's critical stage and the frequency and severity of discomfort symptoms (Wang, Chen, et al, 2016;Wang, Lin, et al, 2016). Therefore, support resources to enhance emotional stability and offer social connection available for paediatric nurses are important to help them dealing with conflicts and hardship in work and life.…”
Section: Discussionsupporting
confidence: 72%
“…The literature does report that working women who lack resources and family connections may be more likely to receive less psychosocial support when encountering difficulties and stress (Alarcon et al., ; Cañadas‐De la Fuente et al., ). Moreover, while paediatric nurses working in general paediatric wards would have more encounters (time and quality) to develop positive and intimate relationship with child‐patients and their families, those working in the CCUs where more invasive and painful procedures and treatments are often needed for the survival of children with critical illness, need to face with the families who often reported experiencing a high level of emotional stress and uncertainty due to their child's critical stage and the frequency and severity of discomfort symptoms (Wang, Chen, et al., ; Wang, Lin, et al., ). Therefore, support resources to enhance emotional stability and offer social connection available for paediatric nurses are important to help them dealing with conflicts and hardship in work and life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They may report feelings of alienation and uncertainty in relation to use of hospital systems and care (Caicedo, ; Simeone et al ., ), and a recent survey reported that the stress levels of primary caregivers with oxygen‐dependent children is high. Predictors of stress include a child's young age, longer hours of daily oxygen therapy and poorer overall health status of the caregiver(s) (Wang et al ., ). Studies examining the experience of parents of children having procedures such as inguinal hernia repair (Wang et al ., ), gastrostomy for feeding difficulties (Pemberton et al ., ) and congenital heart surgery (Simeone et al ., ; Wei et al ., ; Woolf‐King et al ., ) show that parents report emotional problems, including anxiety and depression.…”
Section: Introductionmentioning
confidence: 97%